PENGARUH LAMA PERENDAMAN DENGAN LARUTAN DAUN SALAM (Syzygium polyanthum) SEBAGAI PENGAWET TERHADAP SIFAT FISIK DAGING BROILER - Sari, Siti Hartika; Septinova, Dian; Santosa, Purnama Edy (Jurnal Riset dan Inovasi Peternakan, 2017)
The aims of reasearch to determine the effect of immersion time using salam leaf solution (Syzygium polyanthum) as a preservative of the physical quality of broiler meat. The experimental design used was Completely Randomized Design (RAL) with 4 treatments and 5 replications. Broiler meat used is the chest as much as 20 pieces and salam leaves are used as an salam solution is old salam leaves (dark green color). Treatment given in this research is P0: broiler meat without immersion using salam leaf solution, P1: broiler meat immersion with leaf solution for 20 minutes, P2: broiler meat immersion with salam leaf solution for 40 minutes, P3: broiler meat immersion using a salam leaf solution for 60 minutes. The data obtained in this study was analyzed by using variance analysis (ANOVA). The results showed that the time of immersion by using the leaf of salam (syzygium polyanthum) did not significantly affect the physical quality (pH, Water Holding Capacity, Cooking loss) broiler meat. Key words: long immersion, salam  leaf (Syzygium polyanthum), physical properties of broiler meat and preservative.